62‐3: Design of High‐Performance Tandem Blue Devices for Quantum‐Dot OLED Display. Issue 1 (25th September 2020) - Wang, Linlin; You, Juanjuan; Wu, Chang-Yen; Yan, Guang; Shen, Yongqi; Bo, Bin; Song, Wenfeng; Sun, Li; Quan, Wei; Luo, Chengyuan; Yu, Donghui; Li, Wei; et al.
Abstract : Highly efficient tandem blue OLEDs based on fluorescent materials were developed for quantum dot OLED applications. We optimize the optical micro‐cavity structure for maximal efficiency, and the dependence of luminescence on the thickness uniformity is theoretically and experimentally confirmed with two different type of blue emitters. We also demonstrate that the selection of charge generation layer (CGL) and electrontransporting material adjacent to CGL have significant impact on the electroluminescence performance of the tandem blue OLEDs. Here, a two‐stack tandem blue OLED achieves a current efficiency of 13.3 cd/A with a CIE coordinate of (0.137, 0.047) and a blue index (BI) of 287, which is approximately 1.7 times higher than that of single unit.